Mesenteric Arteriovenous Dysplasia/Vasculopathy Is Distinct From Fibromuscular Dysplasia. (October 2016) - Patil, Deepa T.; Kissiedu, Juliana; Rodriguez, E. Rene; Downs-Kelly, Erinn; Liu, Xiuli; Rybicki, Lisa A.; Tan, Carmela D.
Abstract : Fibromuscular dysplasia (FMD) is a noninflammatory, nonatherosclerotic vasculopathy that usually affects the carotid and renal arteries. We have observed FMD-like vascular changes in specimens resected for ischemia or Crohn's disease (CD). On the basis of a systematic clinicopathologic review of these 11 cases identified between 1982 and 2014, we describe a distinct mesenteric vasculopathy that involves both arteries and veins [mesenteric arteriovenous dysplasia/vasculopathy (MAVD/V)] and is characterized by (1) concentric/eccentric smooth muscle collarette around the tunica media of both the artery and the vein in ≥2 foci, (2) varying degrees of intimal and medial hyperplasia and adventitial fibrosis, and (3) lack of inflammation or thrombi. MAVD/V cases were clinically diagnosed as CD (45%), mass/lesion (27%), ischemia (9%), obstruction (9%), or rectal prolapse (9%). Abdominal pain for >1 year was the most common symptom. Most patients were women (M:F=1:2.7; mean age, 63 y). Mucosal changes mimicking CD, such as architectural distortion (55%), multifocal ulcers (73%), and pyloric gland metaplasia (64%), were common; however, no granulomas or transmural lymphoid aggregates were identified. Ischemic pattern of injury was seen in 4 cases. Upon follow-up (mean, 31.2 mo), 8 patients were found to be asymptomatic, 2 had died of unrelated causes, and 1 was lost to follow-up. We propose the name MAVD/V for a distinct noninflammatory, nonatherosclerotic, localized form of mesenteric vasculopathy that involves both arteries and veins, distinct from FMD. Unlike FMD, surgical resection appears to be curative, with a favorable clinical outcome. Awareness of this vascular entity is important as patients may be potentially misdiagnosed as having CD and ischemic bowel disease.